2023
DOI: 10.3390/plants12040954
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Biofertilizers to Pulse Crops: From Single-Strain Inoculants to New Technologies Based on Microbiomes Strategies

Abstract: Pulses provide distinct health benefits due to their low fat content and high protein and fiber contents. Their grain production reaches approximately 93,210 × 103 tons per year. Pulses benefit from the symbiosis with atmospheric N2-fixing bacteria, which increases productivity and reduces the need for N fertilizers, thus contributing to mitigation of environmental impact mitigation. Additionally, the root region harbors a rich microbial community with multiple traits related to plant growth promotion, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 231 publications
0
9
0
1
Order By: Relevance
“…Previous researchers have found that application of rhizobacteria derived from the soil rhizosphere significantly improved plant growth and increased yield in various tea cultivars under greenhouse or nursery conditions ( Chakraborty et al., 2013 ; Dutta and Thakur, 2017 ). In addition, rhizobacterial application in other cultivated crops increased crop yield and also prevented from fungal disease attack ( Kaymak et al., 2023 ; Xavier et al., 2023 ; Ferioun et al., 2023 ). In the present investigation, we have evaluated PGP activity of the five selected rhizobacteria, namely M. barkeri BPATH02, B. subtilis BNLG01, B. paramycoides BOK01, B. subtilis OKAKP01, and S. maltophilia BSEY01 based on their promising in vitro PGP activity on a tea cultivar TV22 under nursery conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers have found that application of rhizobacteria derived from the soil rhizosphere significantly improved plant growth and increased yield in various tea cultivars under greenhouse or nursery conditions ( Chakraborty et al., 2013 ; Dutta and Thakur, 2017 ). In addition, rhizobacterial application in other cultivated crops increased crop yield and also prevented from fungal disease attack ( Kaymak et al., 2023 ; Xavier et al., 2023 ; Ferioun et al., 2023 ). In the present investigation, we have evaluated PGP activity of the five selected rhizobacteria, namely M. barkeri BPATH02, B. subtilis BNLG01, B. paramycoides BOK01, B. subtilis OKAKP01, and S. maltophilia BSEY01 based on their promising in vitro PGP activity on a tea cultivar TV22 under nursery conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, researchers developed various bio-products based on PGPRs and applied them to diverse cropping systems, such as vegetables ( Kaymak et al., 2023 ), pulses ( Xavier et al., 2023 ), cereals ( Ferioun et al., 2023 ), oil seed crops ( Urooj et al., 2022 ), and plantations crops ( Dutta and Thakur, 2017 ) as microbial biocontrol and biofertilizer agents. Although, in various cropping systems such as common bean ( Remans et al., 2008 ), wheat ( Upadhyaya et al., 2009 ), rice ( Beneduzi et al., 2008 ), and maize ( Cordero et al., 2012 ) genetic diversity of rhizobacteria/PGPRs has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural practices heavily relying on fertilizers and pesticides can deplete soil carbon and fertility, decrease pH, and reduce soil microbial diversity and plant vigor [10][11][12]. Using beneficial microbes is considered a tool to circumvent agricultural intensification [13,14]. Microorganisms have been utilized as biofertilizers, biocontrol agents, and biostimulants over decades.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial soil microorganisms, including plant growth‐promoting rhizobacteria, N‐fixing rhizobia, plant growth‐promoting fungi and arbuscular mycorrhizal fungi (AMF), associated with plant roots can directly or indirectly benefit plants by impacting plant nutrition (biofertilizers), growth (biostimulants) or defence against abiotic and biotic stress (biopesticides and bioremediation; Alori et al, 2017; Elnahal et al, 2022; O'Callaghan et al, 2022; Orozco‐Mosqueda et al, 2022), and are being investigated as potential tools to support sustainable agriculture and reduce chemical fertilizer and pesticide inputs (Batista & Singh, 2021; Li et al, 2022; O'Callaghan et al, 2022; Trabelsi & Mhamdi, 2013; Xavier et al, 2023). Given their importance to crop production, there is considerable interest in manipulating the rhizobiome, either by manipulating microbial recruitment via the plant and associated root exudates, or by manipulating the resident microbial community available for recruitment (Elnahal et al, 2022; Khan, 2022; Orozco‐Mosqueda et al, 2022; Ray et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Field pea, Pisum sativum L. (Fabales: Fabaceae), is an annual, cool season, herbaceous legume that serves as an important source of nutrition for humans and animals (Dahl et al, 2012;Endres & Kandel, 2021;Maxted & Ambrose, 2001;Santos et al, 2019;Xavier et al, 2023) and establishes a symbiotic relationship with N-fixing rhizobia in the Rhizobium leguminosarum species complex (Flores-Félix et al, 2020;Hirsch et al, 2001;Young et al, 2021). Although there is substantial information on N-fixing rhizobia and legumes (Dilworth et al, 2010;Nutman, 1976;Varma et al, 2020), understanding more about how other types of MI impact legumes may contribute to improved, more sustainable production practices (Khan et al, 2010;Xavier et al, 2023). In particular, little is presently known about the efficacy of and interactions of nonrhizobial MI with resident soil biota in field pea (Elnahal et al, 2022;Ibrahim & El-Sawah, 2022;Khan, 2022;O'Callaghan, 2016;Orozco-Mosqueda et al, 2022;Santos et al, 2019).…”
mentioning
confidence: 99%